2020
DOI: 10.1590/s1677-5538.ibju.2019.0842
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical background of ovine kidney for use as animal model: analysis of arterial segmentation, proportional volume of each segment and arterial injury after cranial pole partial nephrectomy

Abstract: Objective: To study the arterial segments of ovine kidney, present a proportional volume analysis of each kidney arterial segment, and analyze arterial injuries caused by simulated partial nephrectomy of cranial pole. Materials and Methods: Forty-eight ovine kidneys injected with polyester resin into the renal arteries and collecting system were used in this study. Eighteen kidneys were used to study the arterial segments and the proportional volume of each renal segment. Other 30 kidneys were submitted to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Simulated partial nephrectomy of the cranial pole in humans and pigs demonstrated that transverse sections less than 1 cm cranial to the hilum promoted significant arterial damage, affecting the mid‐zone arterial supply (Favorito et al, 2011; Pereira‐Sampaio et al, 2012), unlike sheep, which had no significant arterial injury after simulated partial nephrectomy of the cranial pole (Zidde et al, 2020). This study showed that the cranioventral branch of the bovine kidney was damaged only in the transverse section performed inside the hilum, 1 cm caudal to the cranial edge of the hilum, impairing the vascular supply of the remaining renal parenchyma (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulated partial nephrectomy of the cranial pole in humans and pigs demonstrated that transverse sections less than 1 cm cranial to the hilum promoted significant arterial damage, affecting the mid‐zone arterial supply (Favorito et al, 2011; Pereira‐Sampaio et al, 2012), unlike sheep, which had no significant arterial injury after simulated partial nephrectomy of the cranial pole (Zidde et al, 2020). This study showed that the cranioventral branch of the bovine kidney was damaged only in the transverse section performed inside the hilum, 1 cm caudal to the cranial edge of the hilum, impairing the vascular supply of the remaining renal parenchyma (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Simulated partial nephrectomy of the cranial pole in humans and pigs demonstrated that sections closer to the renal hilum affect the arterial supply of the mid‐zone (Favorito, Brito, & Sampaio, 2011; Pereira‐Sampaio, Henry, Favorito, & Sampaio, 2012). On the other hand, simulated partial nephrectomy of the cranial pole in sheep did not show any significant arterial damage (Zidde, Sampaio, Souza‐Junior, De Souza, & Pereira‐Sampaio, 2020). There is no detailed anatomical study on these topics in a bovine kidney, as well as on the proportional analysis of the arterial segments.…”
Section: Introductionmentioning
confidence: 99%